Heart diseases in children a pediatrician's guide - Abdulla, Ra-id (Springer, 2011)
As front line health care providers for children, pediatricians are entrusted with the responsibility for discovering early signs of heart diseases in this complex patient population. Especially in the newborn period, the presentation of pediatric heart disease is frequently obscure, and the consequences of these illnesses can be devastating if not caught early and managed correctly. This comprehensive, easy to understand book is a ready guide to acquiring the proficiency and confidence necessary to decipher the wide spectrum of disease presentations. Case scenarios give life to each chapter, with key images and illustrations reinforcing notable concepts. Special attention is given to the interpretation of chest radiographs and the role of echocardiography and catheterization. All chapters are dual authored by an academic cardiologist and a practicing general pediatrician, resulting in this book's elegant blend of medical authority, real life value, and fresh practical viewpoints. Heart Diseases in Children: A Pediatrician's Guide is divided into four sections. The first is an overall approach to heart diseases in children with ample discussion to diagnostic testing. The second and third sections cover the spectrum of congenital heart defects and acquired heart diseases. The fourth section prsents issues related to office cardiology. The book concludes with an extensive drug appendix. Significant and meaningful online complements, heart sounds and murmurs are available at www.pedcard.rush.edu providing practitioners the materials necessary to build confidence in their ausculatory skills. This unique book is a go-to resource for pediatricians, pediatric residents, family practitioners, medical students and nurses, conveying essential information for the diagnosis and treatment of pediatric heart diseases.